Can the Succession Plan for Family Business Achieve Social Employment Stability? An Analysis from the Perspective of Entrepreneurs - Hongmei Zhang; Mu Xing; Dong Chen (Economies)
Employment stability is crucial to social harmony and individual well-being. This study empirically analyzes whether the succession plan adopted by a family business can achieve the goal of stable employment and explores potential mechanisms at the individual level of entrepreneurs. This paper takes the data from the latest Chinese Private Enterprise Survey as the research sample and employs OLS regression to empirically analyze the impact of family business succession plans on employee employment. The study finds that the succession plan can significantly increase the employment scale of a family business. The pathway mechanism indicates that the employment promotion effect is achieved by enhancing entrepreneurial responsibility and prospect perception. Additionally, when a training method involving different positions within the company is adopted, the succession plan has a more substantial promotion effect on labor employment. Finally, this study analyzes the impacts of the succession plan from three aspects: flexible employment forms, wage income levels, and employee recruitment preferences. Previous studies have not explored whether family enterprises’ formulation of a succession plan will affect social employment. By addressing this issue, new micro-level evidence is provided for further understanding of the relationship between family enterprises and the labor market.